Pelatihan Identifikasi Kandungan Metabolit Sekunder Tumbuhan Menggunakan KIT Rapid Test Skrining Fitokimia Pada Guru di Madrasah Cendekia Bangsa Pekanbaru - Miterianifa; Okmarisa, Heppy; Lubis, Faisal Hariman; Nurbaiti; Ilhami, Aldeva; octarya, Zona (LPPM UMRI, 2026)
The aim of this community service program was to improve science teachers’ knowledge and skills regarding the identification of plant secondary metabolites and phytochemical screening. The program employed a Participatory Action Research (PAR) approach. The participants were 12 science teachers from Madrasah Cendekia Bangsa in Pekanbaru. Data were collected through training sessions, laboratory practice, observations, and questionnaires. The results showed an increase in teachers’ knowledge of plant secondary metabolite identification and phytochemical screening, with an n-gain score of 0.8. Teachers’ skills in conducting phytochemical screening tests of plant secondary metabolites were categorized as very good. In addition, the teachers were able to develop a teaching module on plant secondary metabolite testing using a rapid test phytochemical screening kit. The teachers’ positive responses indicated the perceived importance of understanding plant secondary metabolites for research in the pharmaceutical field. This community service activity specifically addressed teachers’ difficulties in understanding plant secondary metabolites and the limitations of practical equipment in school laboratories.